FESSUD Finance and Well-being Survey: Report - Santos, Ana C. (2016)
The FESSUD Finance and Well-being Survey is part of the EU FP7 FESSUD project – Financialisation, Economy, Society and Sustainable Development. Taking the household as the main unit of analysis, the survey inquired about household sociodemographic characteristics, household income, household debt, household possessions of financial assets, perceived impact of household financial engagements, welfare provision, and perceived impact of the financial crisis and subjective well-being. It consisted of telephone interviews carried out in November and December 2014 with nationally random samples of households in five countries - Germany, Poland, Portugal, Sweden and the UK - selected to be representative of different types of financial system and welfare regime in the EU. For each household, the questionnaire was applied to the individual within the household who declared he or she knew about and was coresponsible for making decisions about the finances of the household. The sample size in the countries ranged from 1300 for Portugal and 1501 for Poland and Sweden, with a total sample of 7009. The survey results indicate that financialisation amplifies extant inequality. In all the countries, household debt and financial assets are concentrated in higher-income households and tend to be a means through which this socioeconomic stratum strengthens its relative advantage. Countries with lower levels of socioeconomic development that have followed such unequal financialisation paths, such as Portugal and Poland, have become more exposed to financial and economic crises, with more detrimental and widespread effects on individual and household well-being.